Sistem Infomasi Pengawasan Sekolah Dasar dan Menengah di Dinas Pendidikan Pemuda dan Olahraga Menggunakan Metode Waterfall - Aan Erlansari; Soni Ayi Purnama; Buhori Muslim; Willi Novrian (INTERNAL (Information System Journal), 2022)
The importance of a computerized system will save more time in managing ongoing business processes and produce accuracy in presenting data or reports to government institutions. The Cianjur Education, Youth, Sports Office requires a data management system for primary and secondary school supervision, namely an Information System that can be used by supervisors to take an inventory of data, including recording, storing, and reporting data from primary and secondary schools. With the information system, the Education, Youth, and Sports Office of Cianjur Regency can see information from schools quickly, precisely, and accurately. Data collection techniques in this study include observation, interviews and documentation. While the research method used is the waterfall method with stages, Communication, Planning, Modeling, Construction, Deployment, Testing. The results of this study are in the form of an analysis design for primary and secondary school supervision information systems using UML design tools, as well as the results of testing the system with the EUCS method.